1993
DOI: 10.1172/jci116900
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypertrophic cardiomyopathy. Microsatellite haplotyping and identification of a hot spot for mutations in the beta-myosin heavy chain gene.

Abstract: Familial hypertrophic cardiomyopathy (FHC) is a clinically and genetically heterogeneous disease. The first identified disease gene, located on chromosome 14qll-ql2, encodes the #-myosin heavy chain. We have performed linkage analysis of two French FHC pedigrees, 720 and 730, with two microsatellite markers located in the #-myosin heavy chain gene (MYO I and MYO II) and with four highly informative markers, recently mapped to chromosome 14qll-ql2. Significant linkage was found with MYO I and MYO II in pedigree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…In the other study, four mutations (R403Q, R453C, R719W, R719Q) were investigated in MYH7 gene and similar to our results none of the mutations were found in patients (n=18) with HCM (27). The R403QLW mutations occurs in close proximity to actin-miyosin interface of the myosin motor domain (28) greatly decrease the actin translocating activity (19) and were associated with high incidence of morbidity and early mortality (29)(30)(31). Although 26 percent of our study population have a family history of sudden cardiac death, we could not find the R403Q mutation in any of the patients.…”
Section: Discussionmentioning
confidence: 61%
“…In the other study, four mutations (R403Q, R453C, R719W, R719Q) were investigated in MYH7 gene and similar to our results none of the mutations were found in patients (n=18) with HCM (27). The R403QLW mutations occurs in close proximity to actin-miyosin interface of the myosin motor domain (28) greatly decrease the actin translocating activity (19) and were associated with high incidence of morbidity and early mortality (29)(30)(31). Although 26 percent of our study population have a family history of sudden cardiac death, we could not find the R403Q mutation in any of the patients.…”
Section: Discussionmentioning
confidence: 61%
“…'-" In some kindreds, the disease has been linked to the f-myosin heavy chain (3-MHC) gene locus on chromosome 14ql. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In these kindreds, HCM has been associated with substitutions of single highly conserved amino acids in the head or head-rod junction of the ,B-MHC molecule. We have previously reported that clinical expression has differed significantly in two kindreds with distinct 3-IMHC gene mutations: The 908``u va1 mutation has been associated with low disease penetrance and a benign prognosis.…”
mentioning
confidence: 99%
“…The near-totality of the missense mutations is localized in the first 23 exons, which encode the globular head and the head-tail junction of the protein 45 . This gene is highly susceptible to mutagenesis in special codons 403, 719, and 741 46,47 . It is suspected that the arginine residue plays a fundamental role in the protein's normal function 46 .…”
Section: Genetic Bases Of Hypertrophic Cardiomyopathy Updatementioning
confidence: 99%
“…This gene is highly susceptible to mutagenesis in special codons 403, 719, and 741 46,47 . It is suspected that the arginine residue plays a fundamental role in the protein's normal function 46 . However, no mutation has a predominant character, although Arg403Gln is a frequent one.…”
Section: Genetic Bases Of Hypertrophic Cardiomyopathy Updatementioning
confidence: 99%
See 1 more Smart Citation